2021
DOI: 10.1099/jgv.0.001618
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Bactrian camel hepatitis E virus by a reverse genetics system

Abstract: Bactrian camel hepatitis E virus (HEV) is a novel HEV belonging to genotype 8 (HEV-8) in the Orthohepevirus A species of the genus Hepevirus in the family Hepeviridae. HEV-8 cross-transmits to cynomolgus monkeys and has a potential risk for zoonotic infection. Until now, neither a cell-culture system to grow the virus nor a reverse genetics system to generate the virus has been developed. To generate replication-competent HEV-8 and to establish a cell-culture system, we synthesized capped genomic HEV-8 RNAs by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Cynomolgus monkeys are susceptible to HEV-5, HEV-7, and HEV-8, but the costs accompanying their use are high, and recent studies indicated that most of the imported cynomolgus monkeys have been exposed to HEV infection, suggesting that the source of the monkey is limited [14]. Our research has confirmed that rats and mice are not susceptible to HEV-8 infection [9]. A tractable small animal remains necessary for this line of research.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Cynomolgus monkeys are susceptible to HEV-5, HEV-7, and HEV-8, but the costs accompanying their use are high, and recent studies indicated that most of the imported cynomolgus monkeys have been exposed to HEV infection, suggesting that the source of the monkey is limited [14]. Our research has confirmed that rats and mice are not susceptible to HEV-8 infection [9]. A tractable small animal remains necessary for this line of research.…”
Section: Introductionsupporting
confidence: 66%
“…All of these HEV strains were produced by a reverse genetics system using a human hepatocarcinoma cell line, PLC/PRF/5 cells (JCRB0406) (JCRB Cell Bank, Osaka, Japan), containing both "quasi-enveloped viruses" and "naked viruses" and that induced infection in cynomolgus monkeys or rabbits. [6,7,9,17]. The culture supernatants of the HEV-infected PLC/PRF/5 cells were clarified by centrifugation at 10,000× g for 30 min and then passed through a 0.45 µm membrane filter (Millipore, Bedford, MA, USA).…”
Section: Hev Strainsmentioning
confidence: 99%
See 3 more Smart Citations